2020
DOI: 10.52006/main.v3i3.213
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurial Competencies and Readiness of Extension Service Beneficiaries of a State University

Abstract: Entrepreneurship as a pillar of a country’s economy improves the quality of life of the people.  Using the descriptive research design, the study aimed to assess the entrepreneurial competencies and readiness of extension and community service beneficiaries of training on transferred technology of a state university in Negros Occidental, Philippines.  A researcher-made questionnaire was utilized to gather data from randomly selected respondents.  Using mean, results showed moderate entrepreneurial competencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
2
0
1
Order By: Relevance
“…Education improves human capital through the acquisition of knowledge and skills from formal institutions. Education improves the entrepreneurial competence of the individual necessary for income diversification (Perez & Guevarra, 2020).…”
Section: Framework Of the Studymentioning
confidence: 99%
“…Education improves human capital through the acquisition of knowledge and skills from formal institutions. Education improves the entrepreneurial competence of the individual necessary for income diversification (Perez & Guevarra, 2020).…”
Section: Framework Of the Studymentioning
confidence: 99%
“…Their path model showed that community service participation affected students' interests. From a state university perspective in the Philippines, Perez et al (2020) also added the association between entrepreneurial competencies and readiness for extension and community service among students. The previous study by Shaka and Senbeto (2018) also found that 72.2 % of the students have an encouraging attitude towards community-based education.…”
Section: Introductionmentioning
confidence: 99%
“…Bir iĢe baĢlamadan önce, giriĢimsel becerilere sahip olmak gerekir. Ayrıca giriĢimci, teknik, yönetim, giriĢimcilik, kiĢisel beceriler gibi tüm yeteneklerini iĢi geliĢtirmek için kullanma becerisine sahip olmalı ve her düzeyde yaratıcı olmalıdır(Wulandari vd., 2021: 311).GiriĢimsel yeteneklerin dolayısıyla giriĢimcilik eğiliminin giriĢimsel hazır bulunuĢluk üzerinde olumlu ve önemli bir etkisi vardır(Seun ve Kalsom, 2015; Acharya ve Chandra, 2019;Perez ve Guevarra, 2020: 116 ve Wulandari vd., 2021.Choo ve Wong (2006), baĢarı ihtiyacı, bağımsız olma arzusu ve kar elde etme güdüsünün giriĢimsel hazır bulunuĢluğa yönelik önemli motive edici unsurlar olduğunu ifade etmiĢlerdir(Olugbola, 2017: 158,159).Korkmaz (2012: 211), giriĢimcilik eğilimi taĢıyan öğrencilerin kendi iĢini kuracakları, bu eğilimi taĢımayanların ise kamu ya da özel sektörde istihdam edilmeyi bekledikleri tespit edilmiĢtir. Ġsmail vd.…”
unclassified